2018
DOI: 10.3390/min8120565
|View full text |Cite
|
Sign up to set email alerts
|

Initial Investigation into the Leaching of Manganese from Nodules at Room Temperature with the Use of Sulfuric Acid and the Addition of Foundry Slag—Part I

Abstract: In this study, the surface optimization methodology was used to assess the effect of three independent variables—time, particle size and sulfuric acid concentration—on Mn extraction from marine nodules during leaching with H2SO4 in the presence of foundry slag. The effect of the MnO2/Fe ratio and particle size (MnO2) was also investigated. The maximum Mn extraction rate was obtained when a MnO2 to Fe molar ratio of 0.5, 1 M of H2SO4, −320 + 400 Tyler mesh (−47 + 38 μm) nodule particle size and a leaching time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 24 publications
4
35
0
Order By: Relevance
“…In the study conducted by Benavente et al [7], it was indicated that no favorable results are obtained by adding O2 for the dissolution of Cu from black copper ore. This situation was improved by working in a reducing condition, which favors the dissolution of MnO2 by means of a reducing agent in an acid medium [11,[25][26][27], allowing subsequent increase in Cu extractions. Figure 4 shows the effect of carrying out a pre-treatment process by adding NaCl, giving a rest time and subsequently leaching the material.…”
Section: Effect Of Nacl Concentration and Cure Timementioning
confidence: 99%
“…In the study conducted by Benavente et al [7], it was indicated that no favorable results are obtained by adding O2 for the dissolution of Cu from black copper ore. This situation was improved by working in a reducing condition, which favors the dissolution of MnO2 by means of a reducing agent in an acid medium [11,[25][26][27], allowing subsequent increase in Cu extractions. Figure 4 shows the effect of carrying out a pre-treatment process by adding NaCl, giving a rest time and subsequently leaching the material.…”
Section: Effect Of Nacl Concentration and Cure Timementioning
confidence: 99%
“…The effects of independent variables on Cu extraction rates from leaching of chalcocite were studied using the response surface optimization method [32][33][34][35]. The central composite face (CCF) design and a quadratic model were applied to the experimental design for Cu 2 S leaching.…”
Section: Experimental Designmentioning
confidence: 99%
“…The Cu extraction rates was studied through the effects of time and chloride and H 2 SO 4 concentrations variables on leaching covellite [37][38][39][40]. An experimental design was carried out considering three levels per factor, resulting in a total of 27 samples [41].…”
Section: Experimental Designmentioning
confidence: 99%